Changing Faces of Change: Metanarratives in the 2016 U.S. Presidential Election - Albion M. Butters (European Journal of American Studies)
This article explores the significance of the theme of “change” in the 2016 U.S. Presidential Election, going beyond its rhetorical use by the candidates or as a way of defining a historic electoral shift (making an “election of change”) to examine how change played a critical role in the political landscape itself. One can locate voters’ desire for change in many existing conditions leading up to the race, but also ideologically and as a force in its own right. Framing of the election as a story reveals that the various actors were increasingly aware of their shifting identities, representations, and agency; thus, change was not just a plot of the story, frequently expressed in terms of populism and popular culture, but a fundamental dynamic behind competing metanarratives and contestations of how the story should be told.